6th DLSU annual institutional service awards - De La Salle University, Manila (Animo Repository, 2017)
The 6th DLSU Annual Institutional Service Awards was held on September 8, 2017 at TYA. Individual pictorial of the awardees was held on July 31, August 2 & 9, 2017 (Manila Campus) at the 11th floor, Archives, Libraries, HSSH and August 8, 2017 (Laguna Campus) at OPM-STC G/F, MDR Bldg. There were 184 academic and support personnel who were honored during the event.